Review: Body Knowledge Performance, Intermediality, and American Entertainment at the Turn of the Twentieth Century, by Mary Simonson - Cisneros, Rosa Maria (The International Journal of Screendance, 2015)
In this book, Mary Simonson examines the American entertainment in the early 1900's, a time of great transformation in which boundaries were challenged and redefined. Her main tool in this examination is "intermediality," a notion which is traditionally found in discussions relevant to media. Simonson argues that intermediality allows one to cast a new look into the past which brings to light things that might have been overlooked. She assists the reader in exploring the interconnectedness between various disciplines, and ultimately enriches the current discourse on performance and musicological values and methodologies. The author highlights that intermediality has often been used to describe new media and postmodernism and in this book she sets out to prove how intermediality lends itself to examining early twentieth-century performances. Simonson's viewpoint offers the reader a bird's eye view on the performers' work in America at the turn of the twentieth century.